Sistem Informasi Layanan Pengaduan Masyarakat Berbasis Web Pada Kantor ATR/BPN Kepulauan Mentawai: Sistem Informasi Layanan Pengaduan Masyarakat Berbasis Web Pada Kantor ATR/BPN Kepulauan Mentawai - Dea Aliza; Wahyuni Yahyan; Harry Setya Hadi (Jurnal Manajemen Teknologi Informatika, 2025)
Fast, transparent, and easily accessible public services are essential in government agencies, particularly in managing public complaints. This study aims to develop a web-based public complaint service information system at the ATR/BPN Mentawai Islands Office to make complaint submission, handling, and monitoring more effective and efficient. The system design applies the Unified Modeling Language (UML) with use case, class, activity, and sequence diagrams to illustrate system needs and workflows, alongside the System Development Life Cycle (SDLC) as a phased development approach. The system is built using PHP and a MariaDB database for user and complaint data storage, with functionality tested through the Black Box method. Key features include user registration, login, complaint submission, and status tracking. All features operate as intended, delivering a transparent and responsive complaint service process. This system prioritizes accessibility, data security, comprehensive features, and structured documentation, successfully improving service quality at the ATR/BPN Mentawai Islands Office.